2011
DOI: 10.1002/dc.21406
|View full text |Cite
|
Sign up to set email alerts
|

A valuable adjunct to FNA diagnosis of papillary thyroid carcinoma: In‐house PCR assay for BRAF T1799A (V600E)

Abstract: The diagnostic approach to thyroid nodules generally starts with FNA cytology. However, approximately one-fifth of cytologic evaluations yield indeterminate cytological findings but only 20% of cases with indeterminate thyroid nodule cytology have a cancer diagnosis, emphasizing the need for an effective ancillary test based on FNA material to help prevent unnecessary surgery. Detection of BRAFV600E mutation, the genetic signature of papillary thyroid carcinoma (PTC) in FNA material provides an invaluable diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…BRAF V600E mutation represents a very specific marker for PTC, also referred to as the “genetic signature of PTC” [ 24 , 25 , 26 ]. As this mutation appears to play an important role in PTC tumorigenesis, it has been postulated that it might also have a prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…BRAF V600E mutation represents a very specific marker for PTC, also referred to as the “genetic signature of PTC” [ 24 , 25 , 26 ]. As this mutation appears to play an important role in PTC tumorigenesis, it has been postulated that it might also have a prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have been published on the feasibility of successfully testing for BRAF mutations using cytologic materials. 7,9,[14][15][16][17][18][19][20] It has been shown that detection of BRAF mutations can be helpful in facilitating accurate diagnosis in thyroid FNA cytology. 5,13 A successful cytologic diagnosis relies on adequate sample with good cellularity.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies were done on histological section while only a few have involved cytologic material. These markers include Ret-PTC translocation, BRAF mutation, K-ras and others [19][20][21][22][23][24]. In summary, unless larger studies are done specifically utilizing molecular markers in FNA material, clinical and cytological features remain the mainstay for diagnosis of follicular thyroid lesions.…”
Section: Discussionmentioning
confidence: 99%